Restraint stress of male mice induces apoptosis in spermatozoa and spermatogenic cells: role of the FasL/Fas system†. Issue 1 (9th April 2019) - Xiao, Bin; Li, Xiao; Feng, Xiu-Yun; Gong, Shuai; Li, Zhi-Bin; Zhang, Jie; Yuan, Hong-Jie; Tan, Jing-He
Abstract: The mechanisms by which psychological stress impairs semen quality are largely unknown. By using a restraint-stressed mouse model, we studied the role of the FasL/Fas system in psychological stress-induced apoptosis of spermatozoa and spermatogenic cells. Male mice were restrained for 48 h before examination for sperm fertilizing potential and for apoptosis and FasL/Fas expression in spermatozoa, spermatogenetic cells/seminiferous tubules, and caudae epididymides. The results showed that the male restraint reduced motility, fertilization rates, and mitochondrial membrane potential while increasing apoptosis and Fas expression in spermatozoa. Restraint also facilitated apoptosis and FasL/Fas expression in spermatogenic cells/seminiferous tubules and caudae epididymides. The restraint-induced apoptosis in spermatozoa and spermatogenic cells was significantly ameliorated in gld mice that harbor a loss-of-function mutation in FasL. However, incubation with FasL did not affect sperm motility and apoptosis, while incubation with tumor necrosis factor (TNF)-α did. The epididymis of the gld mice produced significantly less TNF-α and TNF-related apoptosis-inducing ligand (TRAIL) than that of wild-type mice did after male restraint. Thus, the results confirmed that the FasL/Fas system played an important role in the psychological stress-induced apoptosis of spermatozoa and spermatogenic cells and that FasL triggered sperm apoptosis in epididymis dependently through promoting TNF-α and TRAIL secretion. Abstract : The FasL/Fas system played an important role in psychological stress-induced apoptosis of spermatozoa and spermatogenic cells, and the epididymal FasL triggered sperm apoptosis dependently through promoting TNF-α and TRAIL secretion.